Defocus Discrimination in Video: Motion in Depth. (November 2017) - Petrella, Vincent A.; Labute, Simon; Langer, Michael S.; Kry, Paul G.
We perform two psychophysics experiments to investigate a viewer's ability to detect defocus in video; in particular, the defocus that arises in video during motion in depth when the camera does not maintain sharp focus throughout the motion. The first experiment demonstrates that blur sensitivity during viewing is affected by the speed at which the target moves towards the camera. The second experiment measures a viewer's ability to notice momentary defocus and shows that the threshold of blur detection in arc minutes decreases significantly as the duration of the blur increases. Our results suggest that it is important to have good control of focus while recording video and that momentary defocus should be kept as short as possible so it goes unnoticed.